Study report on consumer preferences for milk and dairy products in the city of Bobo-Dioulasso - Fayama, Tionyélé; Sodre, Etienne; Sib, Ollo; Dabiré, Der (2024)
In Burkina Faso, milk imports not only compete with local milk, but also and more importantly represent a loss of earnings for poorer nations. In view of this, it is necessary to determine how people choose which type of milk to consume. In other words, we need to understand the rationale behind individual and/or collective choices to consume milk and its by-products. This was the guiding principle behind this study, the objectives and results of which are set out below. The study on milk consumption in Bobo-Dioulasso sought to: Identify consumer preferences between milk powder and local milk; Identify consumer preferences for dairy products made from milk powder or local milk; Analyze what drives consumers' rationales and choices.